2020
DOI: 10.1097/md.0000000000023598
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of massage in the treatment of post-stroke insomnia

Abstract: Background : Post-stroke insomnia (PSI) is a serious problem which has significant adverse effects on the subsequent recovery of patients and the quality of their daily life. Massage is effective in improving the quality of sleep for stroke patients displaying no significant adverse reactions. Up to now, however, there are still no systematic studies conducted to provide compelling evidence for its effectiveness in treating PSI. Allowing for this, this project is purposed to make a thorough summar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
(12 reference statements)
0
4
0
Order By: Relevance
“…[20,21] Tuina, as a traditional external therapy in traditional Chinese medicine, can effectively reduce the blood pressure of patients by correcting the dislocation of the neck joints, releasing rigid muscles, and promoting blood circulation. [22,23] However, no systematic review has been conducted to date. This study is the first randomized controlled trial to evaluate the efficacy and safety of massage therapy for the treatment of hypertension with cervical spondylosis.…”
Section: Discussionmentioning
confidence: 99%
“…[20,21] Tuina, as a traditional external therapy in traditional Chinese medicine, can effectively reduce the blood pressure of patients by correcting the dislocation of the neck joints, releasing rigid muscles, and promoting blood circulation. [22,23] However, no systematic review has been conducted to date. This study is the first randomized controlled trial to evaluate the efficacy and safety of massage therapy for the treatment of hypertension with cervical spondylosis.…”
Section: Discussionmentioning
confidence: 99%
“…The alternatives are in varied forms, such as acupuncture, massage, auricular acupoint, catgut embedment in acupoint, the music of 5 phases, Tai Chi, also the decoction including Si Ni San, Tianma Gouteng Yin, Da Ding Feng Zhu, Gui Pi Decoction, Chaihu Longgu Muli Decoction (CLMD), self-designed Ningxin Anshen Formula and so on. [10][11][12][13][14] Especially, Herbal medicine shows a significant efficacy in relieving insomnia. [15] Other treatments like cognitive-behavioral therapy, bright light therapy are also mentioned.…”
Section: Description Of the Conditionmentioning
confidence: 99%
“…After treatment, the patient 's symptoms were found to improve after follow-up, and it was found that the method of abdominal massage can regulate the hypothalamus. In order to prove the effectiveness of massage in the treatment of insomnia, Wang Jing et al [39] collected 78 insomnia patients for clinical observation. In addition to taking estazolam tablets and psychological counseling, the acupoints of the patient 's head and back were massaged.…”
Section: Tuina Treatment Of Insomniamentioning
confidence: 99%